High Levels of Tumor Necrosis Factor-Alpha Reduce Placental Aquaporin 3 Expression and Impair in vitro Trophoblastic Cell Migration - dos Passos Junior, Rinaldo Rodrigues; de Freitas, Raiany Alves; Reppetti, Julieta; Medina, Yollyseth; Dela Justina, Vanessa; Bach, Camila Werle; Bomfim, Gisele Facholi; Lima, Victor Vitorino; Damiano, Alicia E.; Giachini, Fernanda R. (Frontiers in Physiology, 2021)
Placentas from preeclamptic women display augmented tumor necrosis factor-alpha (TNF-α) levels with reduced expression of aquaporin 3 (AQP3). However, whether TNF-α modulates AQP3 expression remains to be elucidated. We hypothesize that elevated levels of TNF-α reduces AQP3 expression and negatively impacts on trophoblastic cell migration. Spontaneously hypertensive rats (SHR) and Wistar (14-16 wk) were divided into hypertensive and normotensive groups. Systolic blood pressure (SBP) was measured, and animals mated. In a third group, pregnant SHRs were treated with a TNF-α antagonist, etanercept (0.8 mg/kg, i.p.) on days 0, 6, 12, and 18 of pregnancy. Placentas were collected on the 20th day of pregnancy. Human placental explants, from normotensive pregnancies, were incubated with TNF-α (5, 10 and 20 ng/mL) and/or etanercept (1 µg/mL). Swan 71 cells were incubated with TNF-α (10 ng/mL) and/or etanercept (1 µg/mL) and subjected to the wound healing assay. AQP3 expression was assessed by western blot and TNF-α levels by ELISA. SBP (mmHg) was elevated in the hypertensive group, and etanercept treatment reduced this parameter. Placental TNF-α levels (pg/mL) were higher in the hypertensive group. AQP3 expression was reduced in the hypertensive group, and etanercept treatment reversed this parameter. Explants submitted to TNF-α exposition displayed reduced expression of AQP3 and etanercept incubation reversed it. Trophoblastic cells incubated with TNF-α showed decreased cell migration and reduced AQP3 expression and etanercept incubation ameliorated it. Altogether, these data demonstrate that high TNF-α levels negatively modulates AQP3 in placental tissue, impairing cell migration, and its relationship in a pregnancy affected by hypertension.